On anti-Peronism and political radicalization: the opposition to the state of internal war (1951-1955) (Quinto Sol, 2020)
After the failed military coup led by Benjamín Menéndez in September 1951, Perón sanctioned the state of internal war, which was not a legal figure included in the Constitution reformed two years ago. This law, in force until the fall of the government in 1955, was justified by the ruling party against the destabilization attempts made by the opposition parties. However, for the anti-Peronist camp, which had been experiencing a process of political radicalization, this figure summarized the growing governmental restrictions of the previous years and consolidated the breakdown of the rule of law.This paper analyzes how the opposition parties to the Peronist government understood the state of war and how their rejection was inscribed in the belligerent political climate that prevailed during the second presidency of Perón. The main hypothesis suggests that the sanction of this law by the Executive Power was decisive for the construction of an anti-Peronist discourse that declared the definitive rupture of democracy. This deepened the preference of opposition groups for extra-institutional strategies to confront the government.
Keywords: peronism; democracy; political identities